Effect of Phenol-Formaldehyde Bonding Agent on Acrylic Resin Impact Strength (Journal of Basic and Applied Research in Biomedicine, 2022)
Objective: evaluating the impact strength of heat-cured acrylic resin material after adding Phenol-formaldehyde (Novolac) as bonding agent material. Materials and Methods: Phenol-formaldehyde blocks were ground into powder, sieved to fine particles to be mixed up with the liquid monomer for 15 minutes, then filtered to be added to the powdered polymer, then the heat-cured acrylic resin was polymerized according to the manufacturer recommendation. Sample of 40 specimens were divided into four main groups (no= 10), Group (A) for heat-cured acrylic resin processed without any additive agent (control group); Group (B): heat-cured acrylic resin processed after adding of 2.5gm of Phenol-formaldehyde powder, Group (C): heat-cured acrylic resin processed with 5gm of Phenol-formaldehyde powder, and Group (D): heat-cured acrylic resin processed with 10gm of Phenol-formaldehyde powder. All the specimens were processed and polymerized by water-bath curing technique and using short curing cycle of 3h. The statistical analysis of variation (ANOVA) and (Games-Howell) test was used at P-value of (P≤0.05). Results: there was a statistically significant difference between the heat-cured acrylic denture base resins that polymerized without additives and that cured with adding of Phenol-formaldehyde as a chemical agent. Conclusion: the heat-cured acrylic resin that polymerized with 2.5gm of Phenol-formaldehyde have the same effect on the impact strength as that polymerized with 5gm of Phenol-formaldehyde.